Towards effective evacuation procedures in disaster management (Dm): Simulation modelling and governance strategies - Noor Akma, Abu Bakar; Noridayu, Mah Hashim; Afrig, Aminuddin; Siti Aishah, Zakaria; Mazlina, Abdul Majid (Universiti Malaysia Pahang, 2023)
Natural catastrophes and disasters may cause the destruction of infrastructure and personal property. In order to reduce the effects of such tragedies, the effectiveness of the evacuation procedures is essential. Effective evacuation procedures, however, also depend on governance issues in addition to technical aspects like infrastructure and communication. This paper intends to review on how governance, and evacuation protocols relate to emergency preparedness and disaster management (DM). Thus, this study explores the use of agent-based and social force theory in developing evacuation simulation models that incorporate evacuation governance strategies. Practitioners and policymakers can better understand the elements that determine the effectiveness of evacuation procedures and create more efficient methods for disaster management and emergency response by modelling human behaviour in disaster circumstances. The policy is an illustration of how governance elements can be integrated into evacuation procedures and guidelines for effective DM. Thus, the expected result for this study emphasises the significance of governance for policymakers and practitioners in the execution of evacuation procedures.